Clinical presentation and complication of chronic suppurative otitis media with cholesteatoma in a rural setting (Mediscope, 2017)
To study the clinical presentations of chronic suppurative otitis media (CSOM) with cholesteatoma and its complication, 96 patients with CSOM from ENT department of a medical college hospital during January 2011 to January 2014 were included in this study. The highest number of cases belonged to the age group of 11-20 years (55.2%), and the number of males and females was 67.2% and 32.8%, respectively. Almost all the patients presented with multiple symptoms. The most common symptoms were discharge from ear(s) (100.0%), hearing impairment (83.3%), earache (15.6%), fleshy mass in ear(s), etc. Of the patients, 67.9% cases were without complication, 26.1% with extracranial complication and 6.3% with intracranial complication. All the cases had a perforation either in the posterior superior marginal (66.5%) or in the attic region (33.5%). Most of the patients were having unilateral CSOM with cholesteatoma, in the right side (64.3%), left side (35.7%), and a few (4.2%) bilateral involvement. Although 83.3% of the patients complained of deafness, audiometric tests were done in 93.7% of the patients excluding 6.4% who had intracranial complication. All of them (93.7% tested) had developed deafness; mild deafness (20.0%), moderate deafness (77.8%), and severe deafness (2.2%). In conclusion, the pattern of clinical presentation and complication of CSOM with cholesteatoma in rural setting may be similar with the pattern involving urban population and early diagnosis of CSOM with cholesteatoma by taking proper history and clinical examination, and timely surgical intervention may be helpful to eradicate the disease and prevent complications.Mediscope Vol. 4, No. 2: Jul 2017, Page 25-28